2001
DOI: 10.1128/mcb.21.5.1737-1746.2001
|View full text |Cite
|
Sign up to set email alerts
|

TFIIA Interacts with TFIID via Association with TATA-Binding Protein and TAF40

Abstract: TFIIA and TATA-binding protein (TBP) associate directly at the TATA element of genes transcribed by RNA polymerase II. In vivo, TBP is complexed with approximately 14 TBP-associated factors (TAFs) to form the general transcription factor TFIID. How TFIIA and TFIID communicate is not well understood. We show that in addition to making direct contacts with TBP, yeast TAF40 interacts directly and specifically with TFIIA. Mutational analyses of the Toa2 subunit of TFIIA indicate that loss of functional interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 90 publications
5
46
0
Order By: Relevance
“…Numerous other Flag-tagged nuclear extracts were also tested in the cross-linking assay, none of which displayed cross-linked polypeptides of shifted mobility. Proteins of note that did not cross-link to the TFIIA NTD include Taf11, previously shown to interact with the TFIIA NTD by two-hybrid assay (Kraemer et al 2001), and Spt3, which genetically interacts with Spt8 and TBP in the SAGA complex (Eisenmann et al 1994).…”
Section: Identification Of Polypeptides That Cross-link To the Tfiia Ntdmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous other Flag-tagged nuclear extracts were also tested in the cross-linking assay, none of which displayed cross-linked polypeptides of shifted mobility. Proteins of note that did not cross-link to the TFIIA NTD include Taf11, previously shown to interact with the TFIIA NTD by two-hybrid assay (Kraemer et al 2001), and Spt3, which genetically interacts with Spt8 and TBP in the SAGA complex (Eisenmann et al 1994).…”
Section: Identification Of Polypeptides That Cross-link To the Tfiia Ntdmentioning
confidence: 99%
“…Later work also showed the importance of other nearby residues on this TFIIA NTD surface. Protein-protein interaction studies using the two-hybrid and GST-pulldown assays suggested that the TFIIA NTD interacts with the TFIID-specific subunit Taf11 (Kraemer et al 2001). This interaction is blocked by mutation of Toa2 residue I27, which also causes a defect in transcription from a subset of genes in vivo (Kraemer et al 2001).…”
Section: A Surface On the Tfiia N-terminal Domain Required For Rapid mentioning
confidence: 99%
See 2 more Smart Citations
“…The binding of TBP to the TATA-box that is located upstream of the 59 untranslated region (59-UTR) initiates the general downstream gene transcription machinery by recruiting a variety of transcription factors including TFIIA, B, E, F, H and J (Kraemer et al, 2001;Ouyang et al, 2000;Pugh, 2000;Vasanthi et al, 2003;Wu & Chiang, 2001). Most of these factors can be identified from the C. parvum genome (http://cryptodb.org/) (data not shown), suggesting that the general gene transcriptional machinery is conserved between this parasite and other eukaryotes.…”
Section: Discussionmentioning
confidence: 99%